What is Light, Really? A Quantum Dialectical View - Malek, Abdul (Annals of Mathematics and Physics, 2024)
Radiant energy in the form of visible light has been and still remains the most mysterious and venerated object in human history. Gradual understanding of the nature of light now in its very wide range of energy, both above and below the visible range; has led to the proliferation of technologies, especially after the recognition of its quantum nature. Although impressive knowledge about the nature of light, its properties, its source, and its interaction with other existing matter, etc., have been gained and profitably utilized in technologies; its fundamental unit as a discrete point particle or an extended continuous wavelet, as well as its mass, still remains a subject of intense debate among the physicists. Understanding the enigmatic properties and the nature of light as difficult as it proved to be; understanding the velocity of its propagation proved to be the most misunderstood aspect of light. As has been shown through some recent publications by this author, the false axiomatic notion of Albert Einstein at the turn of the 20th century, about the universal and absolute constancy (in vacuum) of the velocity c of light; caused the century-long confusion, paradoxes, myths and ironically, the darkest period of modern physics and cosmology! Another wrong centuries-old axiomatic notion of Isaac Newton about the one-sided universal gravitational attraction of matter, acted in a synergistic way with Einstein’s false axiomatic notion about light; to create the modern and sophisticated ruling mythology of the “Big Bang” creation of the universe, undermining scientific progress both in theoretical physics and in cosmology, since Copernicus and Johannes Kepler. It can now be demonstrated that this new mythology has absolutely no basis in objective reality and is the product of brain-cooked and abstract mathematical fabrications based on an axiomatic truth and apparently willful deceptions by official science. A quantum dialectical approach reveals that light is composed of point particles (photons) with a wide range of energy, velocity, and mass; over the whole electromagnetic spectrum, from the microwave to the highest energy gamma-ray photons. The only difference from other matter particles is that photons exist only in their free elementary state and are created instantly (until absorbed) from their virtual existence in matter atoms or in the quantum vacuum; in this infinite, eternal, and ever-changing universe; thereby resolving all mysteries about light.